The Influence Of Market Orientation, Product Innovation And Competitive Prices On Competitive Advantage And Marketing Performance Of Eco-Friendly Household Product Processing In The DKI Jakarta Area - Ikbar, Harits; Rizky, Ananda Mochammad; Usman, Osly (Westscience Press, 2023)
More and more people are turning to environmentally friendly products and services in Indonesia. DKI Jakarta has a large population and demand for eco-friendly household products is increasing. Katadata Insight Center survey shows food is the most purchased environmentally friendly item. Research method is an approach used to obtain scientific data with a specific purpose. In the context of this study, this research is included in the category of quantitative research. Quantitative research is a type of research that uses statistical procedures or other measurement methods to achieve research findings or results. By using quantitative methods, we can obtain the significance of group differences or relationships between the variables under study. Researchers are interested in the influence of market orientation, innovation and competitive prices on eco-Friendly household products. Firm Resources and Sustained Competitive Advantage.